تحريض المخاض بالأوكسيتوسين لدى سوابق قيصرية سفلية واحدة - النقري, محمد; الأيوب, جهاد; بلال, رلى (Latakia University Journal -Medical Sciences Series, 2019)
أجري البحث في مشفى الأسد الجامعي في اللاذقية في الفترة بين 1/4/2008 و1/4/2009 وشمل 114 حاملا" مع سوابق قيصرية سفلية واحدة تعرضت لتجربة مخاض، وقسمت إلى 3 مجموعات : 38 مريضة تركت للمخاض العفوي، 38مريضة تم حث المخاض لديهن بالأوكسيتوسين ،38 مريضة تم تحريض المخاض لديهن بالأوكسيتوسين، وكانت النتائج كما يأتي : المجموعة الأولى تمت الولادة المهبلية بنسبة 76.3% والقيصرية بنسبة 23.7%، المجموعة الثانية تمت الولادة المهبلية بنسبة 84.2%والقيصرية بنسبة 15.8%، المجموعة الثالثة تمت الولادة المهبلية بنسبة 81.5% والقيصرية بنسبة 18.5%، حدثت حالتان لانفتاح ندبة الرحم السابقة: واحدة بعد حث المخاض بالأكسيتوسين والأخرى بعد التحريض بالأوكسيتوسين . نستنج أن تحريض المخاض بالأوكسيتوسين لدى سوابق قيصرية سفلية واحدة قلل من نسبة القيصرية المكررة دون ان تزداد المراضة الوالدية والوليدية بصورة ملحوظة. This research was conducted at AL-ASSAD University Hospital in lattakia between 1/4/2008-1/4/2009 and included 114 pregnant women with one previous low–segment cesarean section experiencing labor. It was divided into three groups: 38 pregnant women had a spontaneous labor, 38 had a stimulation of labor with oxcytocine, 38 had a induction of labor with oxcytiocine., In group (1), the rate of vaginal delivery was 76.3%, and the rate of cesarean section 23.7%. In group (2), the rate of vaginal delivery was 84.2%, and the rate of cesarean section 15.8%. In group (3), the rate of vaginal delivery was 81.5%, and the rate of cesarean section 18.5% . Two cases of scare rupture occurred, one after stimulation of labor with oxcytiocine, and the other after induction of labor with oxcytiocine. In conclusion, labor induction with oxcytiocine in one previous low-segment cesarean section had decreased the rate of repeated cesarean without increasing maternal or fetal morbidity.